The Manifestation of Sovereign Power in the Novel Yauma Qutila al-Zaim by Najib Mahfudz - M. Hafidzulloh S.M; Aprinus Salam (AIBPM Publisher, 2021)
Polemics and social inequality are the primary basis for story building in several of Najib Mahfudz's works. As the primary source, the social constellation presents to seek the formation of relations between social structures and literature. Various social systems come with articulations in economic, cultural, and political forms. This article will explore the context of government and state apart from being an executive institution and exercising sovereignty with its power. The identification of sovereignty is closely related to very paradoxical power. This type of research is qualitative. This type is classified because the primary data source in the study is in the form of textual data from the novel Yauma Qutila al-Zaim by Najib Mahfudz using a postmarxis approach. In this study, two main problems are discussed. First, how is the manifestation of the dual function of state power and sovereignty; second, why sovereignty is placed and positioned as a structure with very high absolutism. The duality formation between sovereignty and power that forms a network of sovereignty with all its forms of transformation. The sovereignty network then includes a working logic of power and sovereignty with all forms of attribution inherent in it.